2013
DOI: 10.1590/s0080-623420130000500018
|View full text |Cite
|
Sign up to set email alerts
|

Patients' knowledge of Diabetes five years after the end of an educational program

Abstract: RESUMOEstudo transversal que teve como objetivos descrever as características sociodemográfi-cas e clínicas e analisar o conhecimento de pacientes com diabetes mellitus sobre o tratamento após cinco anos do término de um programa educativo. Foram entrevistados, em 2010, 40 pacientes que, em 2005, haviam participado de programa de educação em diabetes, oferecido por um período de 12 meses, em um serviço de atenção primária. Utilizou-se formulário contendo: conceito, fisiopatologia e tratamento da doença, exercí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 14 publications
(16 reference statements)
1
10
0
14
Order By: Relevance
“…The demographic and clinical characteristics of the sample studied are consistent with two cross-sectional studies with DM patients receiving outpatient care in the city that was investigated (24)(25) . Full vaccination found was 13.7%, lower than in a retrospective study conducted with a non-institutionalized population in the USA, which showed that hepatitis B vaccination rates were 22.4% from 1999 to 2008 (14) .…”
Section: Discussionsupporting
confidence: 71%
“…The demographic and clinical characteristics of the sample studied are consistent with two cross-sectional studies with DM patients receiving outpatient care in the city that was investigated (24)(25) . Full vaccination found was 13.7%, lower than in a retrospective study conducted with a non-institutionalized population in the USA, which showed that hepatitis B vaccination rates were 22.4% from 1999 to 2008 (14) .…”
Section: Discussionsupporting
confidence: 71%
“…Many diabetic patients had a low education level and some were also illiterate. This finding may negatively influence treatment, because it interferes with the understanding of therapy, and as consequence researches show a lower school level as being associated with the worst levels of adherence to pharmacological and non-pharmacological measures (1)(2)(3)(4) .Given this, the importance of functional health literacy, which is the ability of the individual to follow health guidelines, regardless of his/her educational level, becomes evident, because a person can have a good level of formal instruction, but not follow the health guidelines satisfactorily (15) . Those retired, married or in a common-law marriage prevailed in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is conducted via pharmacological and non-pharmacological measures (2) . The goal is to control blood glucose levels, so that the patient stays symptom-free and does not have acute and chronic complications, promoting quality of life and reducing mortality (3)(4)(5) . In this context, insulin therapy is one of the most important treatments for people with DM and also the one which requires the most care.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing appointment guided by supported self-care orients practice of assistance through three main points: appropriate clinical management of the chronic disease; necessary changes in lifestyle; and appreciation of emotional aspects of patients, including changes in their vision of future, or in the way they handle and face chronic condition and its adversities (6) . Such strategy has already proved to be effective to maintain the knowledge about the disease and its treatment (15) , although it still lacks studies that evaluate its effectiveness on individuals with DM2. With that in mind, the aim of this study is to verify the effect of nursing appointment on the cardiometabolic profile of people with DM2.…”
Section: Introductionmentioning
confidence: 99%